Do Cognitive Test Scores Explain Higher U.S. Wage Inequality? - Francine D. Blau; Lawrence Kahn (Center for Economic Studies and ifo Institute (CESifo), 2004)
Using microdata from the 1994-8 International Adult Literacy Survey (IALS) for nine countries, we examine the role of cognitive skills in explaining higher wage inequality in the United States. We find that while the greater dispersion of cognitive test scores in the United States plays a part in explaining higher U.S. wage inequality, higher labor market prices (i.e., higher returns to measured human capital and cognitive performance) and greater residual inequality still play important roles, and are, on average, quantitatively considerably more important than differences in the distribution of test scores in explaining higher U.S. wage inequality.
Keywords: 330